Static analysis of .NET programs using rewriting rules - Mamedov, T.A.; Doroshenko, А.Yu.; Shevchenko, R.S. (Інститут програмних систем НАН України, 2020)
A software tool that finds problems of resource consumption in case of work with files using rewriting rules was implemented. To reach the goal, the TermWare system, which could be embedded into those systems running on JVM, was used. In order to work with C#-programs, the special plugin for TermWare, which helps to generate appropriate terms from source code, was developed. The plugin uses the Roslyn compiler, which allows users to find syntax errors in programs and focus on the primary task of generating terms from source code. Also, a practical application based on TermWare system – a static analyzer that finds problems with open-close files, was described in the article.Problems in programming 2020; 2-3: 157-163